Corrosión en prótesis porosas de AISI 316L obtenidas por Gelcasting - Gregorutti, Ricardo Walter (2014)
Gelcasting (GC) process, usually used for ceramic moulding, is adapted for producing spongy or porous metal osteosynthesis components destined to bone void filling. The main objective of the interconnected porosity is to improve the osteoconductive of metal matrix by ingrowth of bone. Further, porosity reduces metal density and Young module, which cause bone resorption, leading to implant failure, phenomenon known as stress shielding. The employed GC is based on the formulation of AISI 316L stainless steel powder suspension in an aqueous solution of organic polymers. This suspension is cast into porous ceramic shells, like those used in lost wax technique, wherein the polymer crosslinking is induced by heating. The shells, containing the resulting hydrogel–metal composite, are subjected to thermal cycle in order to dry, burn the organic phase, sinter the metal particles at 1200 °C, and cool down to room temperature under dry hydrogen permanent flow. The susceptibility to corrosion of 50-60 % porous pieces was analyzed. The results indicated that the lower relation between the open porosity and the total porosity, the lower the corrosion rate.